Trinitarian Theology and Power Relations - Minister, M. author. aut Link
X, 224 p.
Keywords: This text crafts a trinitarian theology that reorients theology from presumptions about the immateriality of the Trinity toward the places where the Trinity matters—material bodies in historical contexts and the intersecting ways political and theological power structures normalize and marginalize bodies on the basis of material difference.